2022
DOI: 10.2337/db21-0694
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Predictors and Long-term Impact of Acute Kidney Injury on Progression of Diabetic Kidney Disease in Chinese Patients With Type 2 Diabetes

Abstract: We aim to assess the long-term impact of AKI on progression of diabetic kidney disease and all-cause mortality, and investigate determinants of AKI in Chinese patients with type 2 diabetes (T2D). A consecutive cohort of 9,096 Chinese patients with T2D from the Hong Kong Diabetes Register were followed for 12 years (mean[SD] age 57±13.2 years; 46.9% men; duration of diabetes 5 years). AKI was defined based on the KDIGO criteria using serum creatinine. Estimated glomerular filtration rate measurements were used … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Third, diabetes is a common patient-based risk factor in those undergoing CPB surgery, [15] and diabetic patients who have an AKI episode have a greater risk of developing CKD. [16] Other patient-based risk factors have been investigated in IRI models, such as aging. For example, 12-month old mice show enhanced AKI in response to renal IRI compared to younger mice, despite a baseline of normal renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Third, diabetes is a common patient-based risk factor in those undergoing CPB surgery, [15] and diabetic patients who have an AKI episode have a greater risk of developing CKD. [16] Other patient-based risk factors have been investigated in IRI models, such as aging. For example, 12-month old mice show enhanced AKI in response to renal IRI compared to younger mice, despite a baseline of normal renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have shown that a senolytic HSP90 inhibitor and a senostatic ASK1 inhibitor can be effective in suppressing the progression of DKD associated with an episode of AKI. The clinical relevance of this finding is supported by the knowledge that the incidence of end stage renal disease (ESRD) increases in diabetic patients in proportion to the number of episodes of AKI and their severity [ 10 ]. Applying senotherapies to patients with DKD, particularly those who experience AKI, may significantly reduce the progression to ESRD.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it is proposed that progression of DKD, and particularly TIF, occurs after episodes of ischemia [ 8 , 9 ]. The clinical relevance of this concept is supported by a study of >9000 patients showing that the incidence and frequency of episodes of AKI in diabetes patients correlates with progression to CKD and end-stage renal disease [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a 10-year study of 3679 patients, AKI episode was an important risk factor for the progression of renal function to stage 4 CKD (HR = 3.56, 95% CI 2.76–4.71), and each episode of AKI doubled that risk (HR = 2.02, 95% CI 1.78–2.30) [ 35 ]. Our study showed that the 90-day renal function failure rate was 66.8%, while a retrospective cohort study showed that the 7-day failure rate of renal function recovery in diabetes patients with AKI was about 46.9% [ 36 ]. It can be seen that the short-term renal prognosis of diabetic patients with AKI is poor.…”
Section: Discussionmentioning
confidence: 99%